IMPLEMENTASI KEBIJAKAN PENGEMBANGAN INOVASI PERTANIAN SPESIFIK LOKASI DI BALAI BESAR PENGKAJIAN DAN PENGEMBANGAN TEKNOLOGI PERTANIAN (BBP2TP) BALITBANGTAN - Fina Arpah; Khasan Effendy; Sampara Lukman; Mansyur Mansyur (Jurnal Academia Praja, 2023)
Achieving food security and nutrition is one of the national development priorities that the government is tasked with realizing. In the 2020-2024 RPJMN there are seven National Priorities (PN). The research design is a depiction of the research paradigm, the author chose a qualitative research approach to reveal and discuss the Implementation of the Performance Policy of the Center for Agricultural Technology Assessment and Development (BBP2TP) towards the Development of Location-Specific Agricultural Innovations. In its implementation, there are many things that influence it. One of the crucial things for the development of location-specific technology is how to harmonize technology development between the Research Center and the Agricultural Technology Assessment Center (BPTP). In the implementation of location-specific technology development policies coordinated by BBP2TP, many interests affect (Interest Affected) the Implementation of Location-Specific Agricultural Innovation Development Policies.